Latin, literacy, and the Roman economy - Wilson, AI (Oxford University Press, 2023)
This chapter examines economic structures and activities that helped spread the use of Latin, and of literacy, across the Roman West. Latin was spread to the provinces by the movement of people—settlers and colonists; the army; some kinds of mobile craftsmen (principally miners and potters); traders; and slaves—and also by the movement of documents, inscribed objects, and the practice of inscribing things in Latin. Slaves, if they were not brought up speaking Latin, had to learn it to survive. Traders learned it for commercial advantage, in preference to using interpreters. The evidence for professional interpreters is largely limited to military contexts or to the imperial court. Language learning lowered transaction costs when trading across different linguistic spheres—which long-distance trade in the Empire was bound to do. Craftsmen migrating from core provinces towards the periphery in search of economic opportunity brought their Latin with them. These processes occurred alongside, and sometimes independently of, any impetus from the army or the administrative apparatus of the state to use or learn Latin. But the spread of Latin, and literacy, arguably also helped the growth of the Roman economy: the development of a lingua franca lowered transaction costs in all areas of commerce and trade, while a larger-scale and more complex economy functioned better with written records, and with the investment in human capital that even basic education represented.